A Sociotechnical Approach to Analyze Pharmaceutical Policy and Services Management in Primary Health Care in a Brazilian Municipality - Noemia Liege Maria da Bernardo; Luciano Soares; Silvana Nair Leite (MDPI AG, 2021)
The decentralization of the Brazilian health system required that municipalities took responsibility for the local Pharmaceutical Policy and Services (PPS) system. This article presents and analyses an innovative experience of diagnosis of municipal PPS as a sociotechnical system. We adopted a multi-methods approach and various data sources. Sociotechnical theory was the framework of the methodology of evaluation and design of systems, analyzing the External System (health system, stakeholders, financing) and Internal System (goals, management, workforce, infrastructure, processes, technology and culture). The "objective" component of the PPS system was identified as the central element. The lack of a unified objective and of a central coordination and unmanaged pharmaceutical services prevented integrated internal planning and planning with other sectors. Stakeholders and documents referred only to technical elements of the system: Infrastructure, technical process, and technology. The social components of the workforce and culture were not mentioned. The organizational culture established was the culture of isolation: "Each one does his own". The pharmacists working in the municipal health system did not know each other. There was no integration strategy between pharmacists and their work processes. Consequently, the municipal PPS had limited scope as a public policy. It had constrained the characteristics of PPS as a complex and open system. Understanding the municipal PPS as a sociotechnical system can push the development of a new level of policy and practice to ensure the population's right to the access to and rational use of medicines.